2021
DOI: 10.1093/jat/bkab032
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyl-4-ANPP: A Marginally Active Byproduct Suggesting a Switch in Illicit Fentanyl Synthesis Routes

Abstract: Profiling of the illicit fentanyl supply is invaluable from surveillance and intelligence perspectives. An important strategy includes the study of chemical attribution signatures (e.g. trace amounts of synthesis precursors, impurities/byproducts in seized material, metabolites in biological samples). This information provides valuable insight into the employed synthesis routes at the heart of illicit fentanyl manufacture (previously mainly the so-called Janssen or Siegfried methods), allowing to track and ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…[66] To this end, the development of algorithms geared toward machine-learning for the establishment of analyses capable of linking a sample to its synthetic pathway have been foci of intense research efforts. [67][68][69][70][71][72][73] This emerging field, rapidly developing in analytical chemistry, has found significant application particularly in the forensic analysis of samples associated not only with fentanyls but other chemical warfare agents. [74][75][76][77][78] Throughout this review, great effort has been placed in providing a brief introduction of the synthetic methods used to construct the discussed fentanyls as well as clear schematics that describe these pathways.…”
Section: Fentanyl: the Flagship Synthetic Opioidmentioning
confidence: 99%
“…[66] To this end, the development of algorithms geared toward machine-learning for the establishment of analyses capable of linking a sample to its synthetic pathway have been foci of intense research efforts. [67][68][69][70][71][72][73] This emerging field, rapidly developing in analytical chemistry, has found significant application particularly in the forensic analysis of samples associated not only with fentanyls but other chemical warfare agents. [74][75][76][77][78] Throughout this review, great effort has been placed in providing a brief introduction of the synthetic methods used to construct the discussed fentanyls as well as clear schematics that describe these pathways.…”
Section: Fentanyl: the Flagship Synthetic Opioidmentioning
confidence: 99%
“…4-ANPP is a fentanyl precursor [24]. Phenethyl-4-ANPP has been identified as a byproduct of illicit fentanyl synthesis [25]. The laboratory does not have 4-ANPP or phenethyl 4-ANPP reference materials with which to confirm the identification of these two compounds in the case sample.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Later studies support what our use reports suggested: these 2 compounds likely indicate poorly synthesized fentanyl and impart no important active pharmacological effect. 27 Their presence suggests less opioid effect for the consumer.…”
Section: Overall Trends and Estimatesmentioning
confidence: 99%